Laju Perpindahan Panas Komposit Hibrida - Wawan Saputra, I Gede; Subagia, I.D.G Ary; Sukadana, I Gusti Ketut (Teknik Desain Mekanika, 2021)
Abstract iIn this research, jute and fiberglass were used as composite reinforcement and combined with EPR 174 epoxy matrix and iEPH 555 hardener as composite binder. The combination of jute fiber and fiberglass is determined for a total of 6 layers by ithe manufacturing process method, namely Vacuum Injection Molding (VIM). The Heat Transfer Experiment Test Equipment iBase Unit TQ TD 1002A is used in the testing process to determine the rate of heat transfer in hybrid composites. In this study iit can be concluded that the thickness, material characteristics and temperature difference greatly affect the rate of heat itransfer in transmitting heat of W/m.K. Jute control specimens were specimens with 33.55% higher heat transferability than ifiberglass control specimens and 19.92% epoxy control specimens. While in the laminate variation, the HE1 specimen has the ihighest heat conduction ability of 25.49% compared to the HE4 variation specimen with a heat transferability value of i54.7299W/m.K. Keywords: Composite, Hybrid, Heat Transfer